Penerapan Protocol Eras (Enhanced Recovery After Surgery) Berbasis Bukti Di Ruang Operasi : Systematic Review - Astilia, Astilia (Sahabat Publikasi Kuu, 2024)
ERAS is a protocol that has been used internationally in managing surgical patients. The ERAS protocol includes pre-operative, intra-operative and post-operative phases. The aim of this research is to determine whether the evidence-based ERAS (Enhanced Recovery After Surgery) protocol can be applied in hospital operating rooms. The search method uses several electronic databases such as Google Scholar and PubMed. After screening, 10 articles that met the criteria were read intensively and then analyzed based on content analysis. It was found that the ERAS Protocol was designed to reduce perioperative stress, improve pain management, mobilization and minimize post-operative complications. It was concluded that this protocol can speed up patient recovery and reduce time in hospital which is multidisciplinary and requires coordination between surgeons, nurses, anesthesiologists, physiotherapists and nutritionists.